Integrating Indigenous Knowledge “Sedekah Ramo” into Elementary Social Studies: A Culturally Responsive Teaching Approach - Felly Valiana; Kirana Prama Dewi (The Indonesian Institute of Science and Technology Research, 2026)
Indigenous knowledge, known as